EVALUASI KINERJA DAN TEBAL LAPIS PERKERASAN DENGAN MENGGUNAKAN METODE BINA MARGA 2013 DAN DRAINASE JALAN - Akhmad Widya Priawitama; Rofi Budi Hamduwibawa; Taufan Abadi (Universitas Muhammadiyah Jember, 2019)
Road is an infrastructure which supports and plays an important role in the transportation sector. The improvement of land transportation infrastructure can support the smooth and equitable development in regional and national levels.. Benculuk highway well known as highway of various destinations. With these conditions, it is necessary to evaluate the thickness of the flexible pavement on the road. Therefore a good handling construction of normalization, enhancement or rehalibitation is needed. It will be done optimally if the factors causing the damage are known. The problem in this research is how the performance of the Benculuk highway, how to evaluate the condition of the thickness of the flexible pavement using the 2013 UR 20-year Bina Marga method, and how to evaluate the dimensions of the road drainage channel. This study aims to (1) analyze performance on the Benculuk highway, (2) analyze the flexible pavement conditions with the 2013 UR 20-year Bina Marga method (3) evaluate the dimensions of the road drainage channel. The results of the 2013 Bina Marga pavement thickness calculation obtained a flexible pavement thickness 47.5 cm, WC AC 4 cm, AC BC 13.5 cm, LPA Class A 15 cm. The results of drainage dimensions b 0.9 m and 1.1 m are planned along 2 km of KM Genteng 6 + 400 (left) with a drainage gradient value of 60% and using cemented masonry material.